The Effect of Media and Mancozeb on the Percentage of Seedling Survival and Seedling Growth of Red Jabon (Anthocepalus macrophyllus) - Tati Suharti; Yulianti Bramasto; Naning Yuniarti (Jurnal Perbenihan Tanaman Hutan, 2018)
The obstacles in a nursery are seedling death and un optimal growth of seedling. This study aims to determine the effect of immersion of seedling in mancozeb and media given Trichoderma sp. on the percentage of seedling survival and  seedling growth of red jabon (Anthocepalus macrophyllus). The design of experiment used was completely randomized design (CRD) with 2 factors ie root immersion with and without mancozeb, and seedling media of soil, soil: husk: compost, soil: husk: compost + Trichoderma sp. The results showed that seedling treatment with mancozeb and  media did not give significant differences in seedling survival, percentage of shoot-root ratio and the quality index. The seedling treatments without mancozeb and media of soil: husk: compost (1:1:1) plus Trichoderma sp. produced optimal diameter and biomass while for optimal height was achieved by treatment of mancozeb and media of soil: husk: compost (1:1:1) plus Trichoderma sp.